FRAUD HEPTAGON IN DETECTING FRAUDULENT FINANCIAL REPORTING USING THE METHOD OF BENEISH M-SCORE - Handayani, Deanita; Kusumawardhani, Indra (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2025)
This research examines the determinants of fraudulent financial reporting among banking companies listed on the Indonesia Stock Exchange during the period 2019–2023, employing the Fraud Heptagon Theory and the Beneish M-Score approach. The study seeks to empirically assess the influence of financial stability, personal financial need, external pressure, financial targets, industry characteristics, ineffective oversight, total accruals, board of director changes, the frequency of corporate governance training, and executive director remuneration on the occurrence of fraudulent financial reporting. The results indicate that financial stability, financial targets, and total accruals have a significant impact on fraudulent financial reporting, whereas the remaining variables do not exhibit a statistically significant relationship. This study enhances the understanding of fraud detection in financial disclosures and underscores the necessity of robust oversight and achievable financial objectives to reduce fraudulent behavior. Future studies are encouraged to investigate additional predictors and utilize alternative models to better forecast financial statement fraud.